STRATEGI MEMAHAMI KONSEP BIOLOGI MENGGUNAKAN PENDEKATAN PASANGAN KONSEP - Suroso Adi Yudianto (PAEDAGOGIA, 2010)
In order to goal can achieved effectively, optimum, and meaning for student,the strategic learning from each lesson is necessary probed, although with minimumfacility. This learning respect pedagogic aspects so that can decrease difficulty of theteaching learning process in implementation. Religious approach is new paradigm ofeducation, because it as guide for human life in the world, include understanding the conceptscreation secret of science. The concept mastery can develop to other competencesor values. Guide of religion showed that everything is created pairs by God, both it growin the world and your self, and something which do not knowed so as to you think. Base onthe theory, those concepts pairs can collected become a concept pair scheme (BDKapproach). This research tries to implement a BDK approach for achieving to mastery ofits concepts. Design of the research using experiment method, its sampling are students ofsecondary school in Bandung. Its sampling divide three strata, that is high DANEM, quiteDANEM, and lower DANEM on the receiving new students. Date of the research isprocessed to use statistic of multivariant ANOVA to testing learning result, and usingquestionnaire to student and teacher response. Research results concluding that strategiclearning using BDK approach can enhance out-come of this learning on all strata ofexperiment group are higher than control group as significance different, especiallydeveloping 10 aspects of the concepts comprehension. This learning process is likedstudents and teachers, and they want to implement on other lesson, and then relevancewith strategic aspects to understand of concepts and developing process skills, so thatbenefit to innovation of the religious science education. Other factors which influencingoutcome correlating with worksheet of student, NEM, media, and teacher competenceusing question technics in teaching learning process.